Carmel River - Vinnie Lopez:::Photographer::::::::::::; Steven Domingo:::Photographer:::::::::::: (Carmel, California, 2023)
Carmel River near where it flows into the Pacific Ocean. Carmel is a small beach city on California's Monterey Peninsula, south of the City of Monterey, Ed Ricketts searched the tidepools and shoreline here to collect specimens.